Written on the body: gender, violence and queer desire in Sarah Kane's Cleansed (ex æquo, 2009)
Écrit sur le corps: genre, violence et désire queer dans la pièce Cleansed de Sarah Kane Cet article analise la pièce Purifié (1998) de Sarah Kane, un des plus controverses e plus europeéns des auteurs de théâtre anglais contemporains. Les trois récits de la pièce explorent la permeabilité des identités sexuels e de genre à travers de la metafore centrale de la violence. Cette violence, selon Kane, marque simultanement l’assumption des identités sexuels e de genre mais aussi la liberation de ces normes. L’árticle examine le refus de Kane d’être connoté comme auteur de theatre feministe ou queer dans la perspectif de la mobilité extreme des reconfigurations corporels qu’elle defende dans son oeuvre. Mots-clés Théâtre, violence, reconfiguration corporel, genre, desir queer. I think Cleansed more than any of my other plays uses violence as metaphor Sarah Kane, interview with Nils Tabert (1998) In a much underrated volume of critical essays Feminism Meets Queer Theory (1997), contributors such as Judith Butler, Gayle Rubin and Teresa de Lauretis examine the relationship between this theoretical odd couple from a variety of perspectives. Two general assumptions, however, seem to be shared by many of the contributors to the volume. The first is that while there is a need for a clear theoretical separation between the two areas, it makes theoretical and political sense to combine their approaches in order to deconstruct processes of heteronormativity. As Judith Butler (Butler, 1997: 3) comments «(i)f sexual relations cannot be reduced to gender positions, which seems true enough, it does not follow that an analysis of sexual relations apart from an analysis of gender relations is possible». The second assumption is that this potential for joint work on questions of gender and sexuality is not happening enough in current critical practice. As Elizabeth Weed (Weed, 1997: x) notes in her